Cumulative response curves to enhance interpretation of treatment differences on the Self‐Esteem And Relationship questionnaire for men with erectile dysfunction. (27th September 2012) - Cappelleri, Joseph C.; Zou, Kelly H.; Bushmakin, Andrew G.; Carlsson, Martin O.; Symonds, Tara
Abstract : What's known on the subject? and What does the study add? Studies on erectile dysfunction (ED) therapies rely heavily on patient‐reported outcomes (PROs) to measure efficacy on treatment response. A challenge when using PROs is interpretation of the clinical meaning of changes in scores. A responder analysis provides a threshold score to indicate whether a change in score qualifies a patient as a responder. However, a major consideration with responder analysis is the sometimes arbitrary nature of defining the threshold for a response. By contrast, cumulative response curves (CRCs) display patient response rates over a continuum of possible thresholds, thus eliminating problems with a rigid threshold definition, allowing for a variety of response thresholds to be examined simultaneously, and encompassing all data. With respect to the psychosocial factors addressed in the Self‐Esteem And Relationship questionnaire in ED, CRCs clearly, distinctly, and meaningfully highlighted the favourable profiles of responses to sildenafil compared with placebo. CRCs for PROs in urology can provide a clear, transparent and meaningful visual depiction of efficacy data that can supplement and complement other analyses. OBJECTIVE:   To use cumulative response curves (CRCs) to enrich meaning and enhance interpretation of scores on the Self‐Esteem And Relationship (SEAR) questionnaire with respect to treatment differences for men with erectile dysfunction (ED). PATIENTS AND METHODS:   This post hoc analysis used data from all patients who took at least one dose of study drug and had at least one post‐baseline efficacy evaluation in a previously published 12‐week, multicentre, randomized, double‐blind, placebo‐controlled trial of flexible‐dose (25, 50, or 100 mg) sildenafil citrate (Viagra) in adult men with ED who had scored ≤ 75 out of 100 on the Self‐Esteem subscale of the SEAR questionnaire.   CRCs were used on the numeric change in transformed SEAR scores from baseline to end‐of‐study for each SEAR component.   The horizontal axis of the CRC represented change from baseline on the SEAR score, and the vertical axis represented the percentage of patients experiencing that change or greater.   The differences between CRCs for the sildenafil group vs the placebo group were assessed using the Kolmogorov–Smirov test. RESULTS:   For each of the SEAR components, there was essentially no overlap in the CRCs between the sildenafil group ( n = 113) and placebo group ( n = 115 or 116, depending on the component), showing that a greater percentage of sildenafil recipients compared with placebo recipients had a more favourable change across the spectrum of response thresholds ( P ≤ 0.01).   Previous research showed that a 10‐point score increase is the minimal clinically meaningful improvement for most SEAR components. In the sildenafil vs placebo groups, a ≥10‐point score increase occurred in 72 vs 37% of patients, respectively, on the Sexual Relationship Satisfaction domain, 71 vs 41% on the Confidence domain, 76 vs 49% on the Self‐Esteem subscale, 60 vs 44% on the Overall Relationship Satisfaction subscale, and 75 vs 38% on the Overall score. CONCLUSIONS:   With respect to the psychosocial factors addressed in the SEAR questionnaire, CRCs clearly, distinctly, and meaningfully highlighted the favourable profiles of responses to sildenafil compared with placebo.   CRCs for patient‐reported outcomes in urology can provide a clear, transparent, and meaningful visual depiction of efficacy data that can supplement and complement other analyses.